Heterozygous Deletion of Epilepsy Gene KCNQ2 Has Negligible Effects on Learning and Memory - Tracy, Gregory C.; Wilton, Angelina R.; Rhodes, Justin S.; Chung, Hee Jung (Frontiers in Behavioral Neuroscience, 2022)
Neuronal Kv7/KCNQ potassium channels underlie M-current that potently suppresses repetitive and burst firing of action potentials. They are mostly heterotetramers of Kv7.2 and Kv7.3 subunits in the hippocampus and cortex, the brain regions important for cognition and behavior. Underscoring their critical roles in inhibiting neuronal excitability, autosomal dominantly inherited mutations in KCNQ2 and KCNQ3 genes are associated with benign familial neonatal epilepsy in which most seizures spontaneously remit within months without cognitive deficits. De novo mutations in KCNQ2 also cause epileptic encephalopathy, which is characterized by persistent seizures that are often drug refractory, neurodevelopmental delay, and intellectual disability. Heterozygous expression of epileptic encephalopathy variants of KCNQ2 is recently shown to induce spontaneous seizures and cognitive deficit in mice, although it is unclear whether this cognitive deficit is caused directly by Kv7 disruption or by persistent seizures in the developing brain as a consequence of Kv7 disruption. In this study, we examined the role of Kv7 channels in learning and memory by behavioral phenotyping of the KCNQ2+/- mice which lacks a single copy of KCNQ2 but does not display spontaneous seizures. We found that both KCNQ2+/- and wild-type mice showed comparable nociception in the tail flick assay and fear-induced learning and memory during a passive inhibitory avoidance test and contextual fear conditioning. Both genotypes displayed similar object location and recognition memory. These findings together provide the evidence that heterozygous loss of KCNQ2 has minimal effects on learning or memory in mice in the absence of spontaneous seizures.